Galleria mellonella as a screening tool to study virulence factors of Aspergillus fumigatus. Issue 1 (31st December 2021) - Durieux, Marie-Fleur; Melloul, Élise; Jemel, Sana; Roisin, Lolita; Dardé, Marie-Laure; Guillot, Jacques; Dannaoui, Éric; Botterel, Françoise
ABSTRACT: The invertebrate Galleria mellonella has increasingly and widely been used in the last few years to study complex host–microbe interactions. Aspergillus fumigatus is one of the most pathogenic fungi causing life-threatening diseases in humans and animals. Galleria mellonella larvae has been proven as a reliable model for the analysis of pathogenesis and virulence factors, enable to screen a large number of A. fumigatus strains. This review describes the different uses of G. mellonella to study A. fumigatus and provides a comparison of the different protocols to trace fungal pathogenicity. The review also includes a summary of the diverse mutants tested in G. mellonella, and their respective contribution to A. fumigatus virulence. Previous investigations indicated that G. mellonella should be considered as an interesting tool even though a mammalian model may be required to complete and verify initial data.